Ahmed bin Youssef Al-Malyani and his tomb The field and the sacred between physical presence and moral evangelism Through the texts of virtues and provisions - barkat, Ismail (The Algerian Historical Journal, 2026)
This research paper seeks to identify the space of the mausoleum of Ahmad bin Yusuf al-Malyani ( d. 931 AH / 1524 AD ), by using it on syllabary and jurisprudential texts, to reveal its patterns and realistic manifestations in space, time and people, and through its extensions, symbols and rituals, and to ask about the methods that the mystic inside invested in transforming His Holiness refers to perceptions, concepts, and practices, as he reveals the shortcomings of its texts in expressing the founder of its sacred field, and giving it news loaded with naive dignities, and that the continuation of writing in it until the 19th century AD within the colonial ethnographic and historical researches constituted the centrality of visiting the shrines of the saints and stationed in the post-Almohad human.